QUALITE PHYSICO-CHIMIQUE DES SOLS AGRICOLES DE LA REGION DE L’OULJA ENTRE SIDI ABED ET OULAD GHANEM (SAHEL DES DOUKKALA, MAROC) - Hajar Mohcine; Najib Saber; Kaoutar Moustarhfer; Fadwa Rafik; Fatna Zaakour; Fatimaezzahra Matech; Chakib Marrakchi (European Scientific Journal, ESJ, 2015)
The present work is a contribution to the characterization of agricultural soils in the region of Oulja (Sahel Doukkala) between Sidi Abed and Oulad Ghanem. This region is considered as a very important agricultural center, known nationally for its high potential of maraichere culture. However, once the plots are destined to these last, they know a significant regression, probably related to changes in soil quality. Therefore, a sampling compaign was done in October 2014 in three stations, in order to evaluate the agronomic quality of soil in the region. Soil quality has been appreciated through some physical and chemical indicators to know: pH, organic matter, calcium carbonates and structural stability in dry and in water. Results indicate that the pH is basic with grades ranging from 8.2 to 8.4 on average, calcium carbonate rates are high in the various stations and greatly exceed 23%, organic matter contents ranging on average of 2.5% to 4.11%, rate of unstable aggregation in water remains below 30%.